Considerations for Effective Lidar Deployment by Transportation Agencies. Issue 1 (January 2014) - Chang, Jeffrey C.; Findley, Daniel J.; Cunningham, Christopher M.; Tsai, Mary K.
Lidar is becoming increasingly popular across the United States, and state transportation agencies are adopting this technology for practical uses in transportation-related applications. This trend can be seen in the growing number of agencies acquiring lidar scanners and contracting lidar services. The primary factors behind this trend are that (a) surveyors, engineers, and technicians are becoming more educated about and increasingly open to lidar and its applications and (b) lidar is potentially more cost-effective than traditional surveying technologies. Lidar can provide transportation agencies with the benefits of safety, data collection productivity, cost-effectiveness, applicability, high levels of detail, and technological advancement. Many of the more practical uses and benefits of lidar have come to fruition in recent years, and transportation agencies have been more open to its use. However, little more than anecdotal evidence supports when a specific lidar platform should be applied for various applications rather than a traditional surveying method. Decision makers in geomatic and surveying departments that use lidar must regularly weigh the options of which surveying method to use for specific projects and base decisions on performance tradeoffs. The methodology presented in this paper aims to provide guidance on how agencies may determine whether lidar can be practically used within their organizations. The aspects and performance measures outlined for effective deployment of lidar equipment or contracted services should be systematically considered.